Pengaruh Kualitas Layanan Inti dan Tambahan terhadap Positive Word of Mouth di SMU Semarang - Nuryatno, Yulius Jatmiko (Jurnal Ilmu Ekonomi ASET, 2011)
Every company will face tight competition with other companies. One ofthe best efforts to keep and get customers is by managing core service quality, peripheralservice quality and word of mouth. This research was done to examine the influence ofthe core service quality and peripheral service quality to the positive word of mouth. Theobject of the research was students of SMA Sint Louis Semarang. The sampling techniqueused was proportional sampling. The samples were 81 samples. The data collection wasobtained by distributing questionnaire to the students. The data survey was organized byusing regression analysis assisted by SPSS program. The result showed that independentvariable of the core service quality positively and significantly influence the positiveword of mouth, while independent variable of peripheral service quality positivelyinfluence but not significantly to the positive word of mouth. It means the first hypothesis(H1) proposed was accepted. The limitation of the research was because some respondentsdid not answer the open questions, so the researcher hardly finds out the respondentsâwants to the service quality expected in SMA Sint Louis.Keywords: core service quality, pheripheral service quality, and positive word of mouth